2 - Globalisation and Internationalisation of Higher Education in South Africa: The Challenge of Rising Xenophobia* - Sichone, Owen (Journal of Higher Education in Africa, 2006)
The internationalisation of university education globally has coincided with the opening up of post-apartheid South Africa to the world market, and the number of foreign students (along with other visitors to South Africa) has shot up very rapidly since 1994. As a member of the Southern Africa Development Community (SADC), South Africa has an agreement (the Education Protocol) with its partners to cooper- ate in the area of education and training. In the absence of a similar spirit of coop- eration allowing for the free movement of citizens of the SADC region, however, the wishes expressed in the Education Protocol cannot be fully realised, and many African students studying in South Africa still have to navigate long and difficult bureaucratic channels to obtain student visas and study permits. In addition, they face an increasingly hostile and xenophobic public on and off campus. Their expe- rience will not provide them with fond memories of their student days in South Africa. This paper advocates greater freedom of movement for migrant students as a means of social upliftment and greater pan-African cooperation.